Extent of Knowledge of Coconut Farmers in Kozhikode District of Kerala - Mathew, Greeshma Susan; Allan, Thomas (Journal of Extension Education, 2021)
The present study was conducted among the coconut farmers of Kozhikode district of Kerala to assess the extent of knowledge on coconut cultivation. A total 120 farmers from purposively selected eight panchayats of the district formed the sample. Extent of knowledge of the farmers was measured using a teacher-made test. Based on analysis of data, it was found that more than half of the farmers possessed medium level of knowledge about the recommended coconut farming practices.